Characteristics, Health Literacy and Self-Stigma on People Living with HIV and AIDS in Kupang City - Imelda Februati Ester Manurung (Health Notions, 2022)
People living with HIV and AIDS (PLWHA) are at risk of having low antibodies that can cause comorbidities such as Tuberculosis (TB) and other diseases. For this reason, this study aims to describe health literacy and self-stigma of PLWHA. This type of research was quantitative with a descriptive design. The sample size was 50 people living with HIV infected with TB, selected using total population sampling. Data collection by using a questionnaire. Data were analyzed descriptively. The results showed that the characteristics of respondents based on age were mostly in the category of more than 31 years (62%), male gender (54%) and self-employed/farmer/fishermen (60%). The majority of PLWH are male, aged above 30 years, have a self-employed job and a high school education above. Health literacy about HIV and TB is mostly in the poor category and self-stigma in the high category. For this reason, it is necessary to improve communication, information and education for PLWHA to improve health literacy and reduce self-stigma.Keywords: health literacy; self stigma; HIV and AIDS